Republic of Slovenia : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This paper provides a background on the key policy challenges for Slovenia in the euro zone. Then, it assesses the discretionary scope to adjust spending and proposes initial steps to enhance budget flexibility so that fiscal adjustment can be targeted on relatively inefficient spending. This study also discusses the long-term fiscal sustainability position of Slovenia using a generational accounting framework. A simulation of retirement incentives suggests that the pension system will encourage individuals to retire earlier than the statutory full pensionable age. These incentives are stronger for low-income earners.